Telehealth by Nursing Practitioners in the Archipelago: Bridging Healthcare Gaps Through Digital Innovation - Yuliyana, Rian; Daswito, Rinaldi; Ilmaskal, Radian (RRZ Scientific Publishing, 2025)
This article examines prominent concerns about using telehealth by nursing practitioners in the archipelago. Implementation of telehealth, defined as technologies that enable patients and clinicians to exchange information about their health state remotely. Telehealth was initially developed to reach rural and underserved populations, providing basic care. This article discusses the advantages and obstacles of telehealth for nursing practitioners in the archipelago. Many articles indicate that the use of telehealth for practicing nurses presents numerous barriers, including personal barriers. Conversely, telehealth offers improved patient access, cost savings, and better outcomes through increased patient engagement. Therefore, nurses preparing for this need to be prepared with telehealth education, practical experience, and consistent integration into their professional development.